Menganalisis Kinerja Keuangan: Dampak Struktur Modal, Pertumbuhan Penjualan, Perputaran Aktiva Tetap, dan Ukuran Perusahaan (Studi Kasus Pada Industri Material Konstruksi di BEI 2019-2024) - Afriza, Deby; Susandini, Aprilina (Trunojoyo University of Madura, 2025)
The purpose of this study was to analyze the effect of capital structure, sales growth, fixed asset turnover, and company size on financial performance, both simultaneously and partially. This research uses quantitative methods with multiple linear regression analysis. The data used is secondary data from the Indonesia Stock Exchange (IDX) with purposive sampling technique, resulting in a sample of 6 companies from a population of 13 companies. The F test results show that simultaneously, capital structure, sales growth, fixed asset turnover, and company size have a positive and significant effect on the company's financial performance in the construction material industry on the IDX for the 2019-2024 period. The T test results show that: Capital structure has a negative and significant effect on the company's financial performance. Sales growth has a positive and significant effect on the company's financial performance. Fixed asset turnover has a positive and significant effect on the company's financial performance. Company size has no significant effect on the company's financial performance. The coefficient of determination (R²) is 0.661, which means that the independent variables in this study explain 66,1% of the variation in financial performance, while 33,9% is explained by other variables outside the research model.